Alterações histopatológicas na mucosa gástrica e nível sérico de gastrina em pacientes chagásicos com e sem infecção pelo Helicobacter pylori - SOUSA, Jacqueline Batista (2015)
.Chagasic patients with digestive form have abnormally high gastrin release and low gastric acid secretion. Likewise, H. pylori infection can also induce hypergastrinemia. Thus, we aimed to evaluate whether hypergastrinemia occurs in patients with the other clinical forms of Chagas disease, co-infected or not by H. pylori. Moreover, serum gastrin levels were associated with CagA-positive H. pylori strains and with gastric histological and endoscopic features. The patients evaluated were divided into two groups, one group comprising chagasic (with digestive form) and non-chagasic patients undergoing upper endoscopy and the other group comprising chagasic (with different clinical forms) and non-chagasic patients who did not underwent this procedure. H. pylori (HP) infection was assessed by histology, detection of 16S rRNA gene in gastric tissue by PCR, serology and the 13C-urea breath test. Gastrin concentration was measured by chemiluminescence assay. CagA expression was examined by PCR. Histological scores were evaluated according to Update Sydney System. The mean serum basal gastrin was significantly higher among chagasic than non-chagasic patients who underwent upper endoscopy than those who did not (p<0.05). No significant differences in the basal serum gastrin concentrations were observed among the different clinical forms of Chagas disease neither among HP-positive and HP-negative patients, chagasic or controls. Patients with digestive form or with the other clinical forms of Chagas disease have increased basal serum gastrin level. Moreover, our findings do not support a direct role of H. pylori infection in the increasing gastrin secretion among chagasic patients.